Modified fluorinated silicone rubber and preparation method thereof, sizing material composition for waterproof coiled material, waterproof coiled material and preparation method and application of waterproof coiled material
By preparing modified fluorosilicone rubber and combining it with other materials to prepare a rubber composition for waterproof membranes, the problems of poor weather resistance and thermal stability of waterproof membranes are solved, and better physical properties and simplified production processes are achieved.
Patent Information
- Application Number
- CN202411219794.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-02
AI Technical Summary
Existing waterproof coils have problems with poor weather resistance and thermal stability, especially when long-term exposure to air, the physical properties will be greatly reduced.
By preparing modified fluorosilicone rubber, using graphite, filler and silane coupling agent for the first mixing, and then performing the second mixing with fluorosilicone rubber, and performing extrusion and granulation treatment, the modified fluorosilicone rubber is obtained. The modified fluorosilicone rubber is used to prepare a rubber composition for waterproofing membranes. It is combined with polyolefin elastomer, linear low density polyethylene, polypropylene, cross-linking agent and cross-linking accelerator, and is obtained by contact mixing and extrusion molding. Waterproof membrane.
Modified fluorosilicone rubber makes the waterproof membrane have excellent weather resistance and thermal stability, avoiding the performance degradation caused by the agglomeration of nano-calcium carbonate. The process is simple and easy to mass-produce.
Smart Images

Figure BDA0005022678970000071 
Figure BDA0005022678970000081 
Figure BDA0005022678970000082
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer waterproof coiled materials, and in particular to a modified fluorosilicone rubber and a preparation method thereof, a rubber composition for waterproof coiled materials, a waterproof coiled material and a preparation method and application thereof. Background Art
[0002] The main raw material of exposed waterproof membrane is polyolefin elastomer. Since the material contains double bond structure, it will react with oxygen if exposed to air for a long time, and the physical properties of the waterproof membrane will be greatly reduced. The current technology is to improve the overall weather resistance of the waterproof membrane by adding anti-aging additives, but anti-aging additives have the disadvantages of precipitation and high price.
[0003] CN110982160A discloses a method for preparing a weather-resistant PE sheath material for photovoltaics, which comprises: (1) putting LLDPE, homopolypropylene, antioxidant, DCP, and cross-linking agent into a high-speed mixer, mixing them evenly, and then putting them into a twin-screw extruder for extrusion granulation, which is called material A; (2) putting fluorosilicone rubber, fatty alcohol polyoxyethylene polyoxypropylene ether, HDPE, carbon black, and antioxidant into a mixer, mixing them, discharging them, and then putting them into a twin-screw extruder for extrusion granulation to obtain a fluorosilicone rubber masterbatch, which is called material B; (3) putting material A, material B, LLDPE, homopolypropylene, nano-calcium carbonate, and POE into a high-speed mixer, mixing them evenly, and then putting them into a twin-screw extruder for extrusion granulation to obtain a PE sheath material for photovoltaics. This method will cause the nano-calcium carbonate to agglomerate in the fluorosilicone rubber, resulting in a decrease in the tensile strength retention rate after artificial weathering.
[0004] CN110982160A discloses a conductive rubber composition, comprising the following components in parts by mass: 50 to 100 parts of silicone rubber, 20 to 80 parts of fluororubber, 100 to 400 parts of conductive filler, 0.5 to 4 parts of vulcanizing agent, and 3 to 15 parts of silane coupling agent. The crosslinking reaction of this solution needs to be completed at a high temperature, and directly involving the silane coupling agent in the crosslinking reaction will lead to the decomposition of the silane coupling agent, and finally cause the conductive filler to agglomerate in the fluororubber and silicone rubber, affecting the tensile strength retention performance and dimensional change rate after aging. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of poor weather resistance and thermal stability of the waterproof roll material in the prior art.
[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a modified fluorosilicone rubber, the method comprising:
[0007] S1, mixing graphite, filler and silane coupling agent for the first time to obtain a mixture I; the conditions of the first mixing include: a temperature of 65-75° C. and a time of 1.5-3 h;
[0008] S2, mixing the fluorosilicone rubber and the mixture I for a second time to obtain a mixture II; the conditions of the second mixing include: a temperature of 165-190° C. and a time of 5-20 min;
[0009] S3, extruding and pelletizing the mixture II to obtain the modified fluorosilicone rubber;
[0010] Relative to 100 parts by weight of the fluorosilicone rubber, the amount of the filler is 10-20 parts by weight, the amount of the graphite is 1-10 parts by weight, and the amount of the silane coupling agent is 1-3 parts by weight.
[0011] The second aspect of the present invention provides a modified fluorosilicone rubber prepared by the method described in the first aspect.
[0012] The third aspect of the present invention provides a sizing composition for waterproofing coiled materials, wherein the composition contains the following components which are stored separately or in a mixture of two or more:
[0013] Polyolefin elastomer, linear low-density polyethylene, polypropylene, modified fluorosilicone rubber, crosslinking agent, crosslinking accelerator;
[0014] Relative to 100 parts by weight of the polyolefin elastomer, the content of the linear low-density polyethylene is 35-65 parts by weight, the content of the polypropylene is 2-18 parts by weight, the content of the modified fluorosilicone rubber is 1-15 parts by weight, the content of the crosslinking agent is 1-5 parts by weight, and the content of the crosslinking accelerator is 0.5-5 parts by weight;
[0015] The modified fluorosilicone rubber is the modified fluorosilicone rubber described in the second aspect.
[0016] The fourth aspect of the present invention provides a method for preparing a waterproof roll material, which is carried out using the composition described in the third aspect, comprising:
[0017] (1) contacting and mixing a composition containing a polyolefin elastomer, a linear low-density polyethylene, a polypropylene, a modified fluorosilicone rubber, a crosslinking agent, and a crosslinking accelerator to obtain an intermediate material;
[0018] (2) The intermediate material is sequentially extruded, molded, and rolled up to obtain the waterproof roll material.
[0019] The fifth aspect of the present invention provides a waterproof roll material prepared by the method described in the fourth aspect.
[0020] The sixth aspect of the present invention provides application of the waterproof membrane described in the fifth aspect in the field of building waterproofing.
[0021] The waterproof coiled material prepared by using the modified fluorosilicone rubber provided by the present invention can simultaneously have excellent weather resistance and thermal stability; compared with the prior art, the production process is simpler and mass production is easier to achieve. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] As mentioned above, the first aspect of the present invention provides a method for preparing a modified fluorosilicone rubber, the method comprising:
[0024] S1, mixing graphite, filler and silane coupling agent for the first time to obtain a mixture I; the conditions of the first mixing include: a temperature of 65-75° C. and a time of 1.5-3 h;
[0025] S2, mixing the fluorosilicone rubber and the mixture I for a second time to obtain a mixture II; the conditions of the second mixing include: a temperature of 165-190° C. and a time of 5-20 min;
[0026] S3, extruding and pelletizing the mixture II to obtain the modified fluorosilicone rubber;
[0027] Relative to 100 parts by weight of the fluorosilicone rubber, the amount of the filler is 10-20 parts by weight, the amount of the graphite is 1-10 parts by weight, and the amount of the silane coupling agent is 1-3 parts by weight.
[0028] Preferably, in step S1, the first mixing is performed in the presence of a solvent.
[0029] Preferably, the amount of the solvent is 140-160 parts by weight relative to 100 parts by weight of graphite; more preferably, the solvent is ethanol.
[0030] More preferably, in step S1, the first mixing operation method comprises: first mixing the silane coupling agent with the material containing the solvent, the filler and the graphite in a dropwise manner; preferably, the dropping speed is 0.1-0.3 ml / s.
[0031] Preferably, before the second mixing, the mixture I is first dried to obtain a mixture I having a solvent content of no more than 0.01 wt %.
[0032] Preferably, the second mixing is performed under stirring conditions, and the stirring conditions include: a stirring speed of 40-60 rpm.
[0033] Preferably, the fluorosilicone rubber has a Shore A hardness of 40-60, a tensile strength of 9-10 MPa, and an elongation at break of 300%-400%. The inventors found that under this preferred embodiment, the waterproof roll obtained by the present invention has better weather resistance and thermal stability.
[0034] Preferably, the average particle diameter of the filler is 7-13 μm.
[0035] More preferably, the filler is calcium powder.
[0036] In order to give the waterproof membrane better weather resistance and thermal stability, preferably, the silane coupling agent uses a silane coupling agent with an amino functional group, such as at least one selected from KH-550 silane coupling agent, KH-470 silane coupling agent, KH-792 silane coupling agent, KH602 silane coupling agent, KH580 silane coupling agent, Si-902 silane coupling agent, and ND-42 silane coupling agent.
[0037] As mentioned above, the second aspect of the present invention provides a modified fluorosilicone rubber prepared by the method described in the first aspect.
[0038] As mentioned above, the third aspect of the present invention provides a sizing composition for waterproofing coiled material, wherein the composition contains the following components which are stored separately or in a mixture of two or more thereof:
[0039] Polyolefin elastomer, linear low-density polyethylene, polypropylene, modified fluorosilicone rubber, crosslinking agent, crosslinking accelerator;
[0040] Relative to 100 parts by weight of the polyolefin elastomer, the content of the linear low-density polyethylene is 35-65 parts by weight, the content of the polypropylene is 2-18 parts by weight, the content of the modified fluorosilicone rubber is 1-15 parts by weight, the content of the crosslinking agent is 1-5 parts by weight, and the content of the crosslinking accelerator is 0.5-5 parts by weight;
[0041] The modified fluorosilicone rubber is the modified fluorosilicone rubber described in the second aspect above.
[0042] Preferably, relative to 100 parts by weight of the polyolefin elastomer, the content of the linear low-density polyethylene is 40-60 parts by weight, the content of the polypropylene is 5-15 parts by weight, the content of the modified fluorosilicone rubber is 3-10 parts by weight, the content of the cross-linking agent is 1-3 parts by weight, and the content of the cross-linking promoter is 0.5-3 parts by weight. The inventors have found that under this preferred embodiment, the waterproof roll obtained by the present invention has better weather resistance and thermal stability.
[0043] More preferably, the melt index of the polyolefin elastomer is 1.0-4.0 g / 10 min.
[0044] Preferably, the polypropylene has a degree of polymerization of 4000-10000, a density of 0.88-0.92 g / cm3, and a melt index of 2.0-4.0 g / 10 min.
[0045] Preferably, the linear low-density polyethylene has a density of 0.90-0.94 g / cm3 and a melt index of 1.0-4.0 g / 10 min.
[0046] Preferably, the cross-linking agent is selected from at least one of sulfur, organic peroxide, melamine formaldehyde resin, urea formaldehyde resin and phenol formaldehyde resin.
[0047] Preferably, the cross-linking promoter is selected from at least one of diethylamine, zinc oxide and divinylbenzene.
[0048] As mentioned above, the fourth aspect of the present invention provides a method for preparing a waterproof roll material, which is carried out using the composition described in the third aspect, comprising:
[0049] (1) contacting and mixing a composition containing a polyolefin elastomer, a linear low-density polyethylene, a polypropylene, a modified fluorosilicone rubber, a crosslinking agent, and a crosslinking accelerator to obtain an intermediate material;
[0050] (2) The intermediate material is sequentially extruded, molded, and rolled up to obtain the waterproof roll material.
[0051] Preferably, the contact mixing is carried out under stirring conditions, and the contact mixing conditions include: temperature of 60-100° C., rotation speed of 30-60 rpm, and time of 0.5-1.5 h.
[0052] Preferably, in step (2), the extrusion molding is performed by three-roll calendering, and the conditions of the extrusion molding include: the temperature of the three rolls is 30-50° C., and the gap between the three rolls is 0.9-1.5 mm.
[0053] In the present invention, the winding is carried out by conventional methods in the art, which will not be described in detail herein, and those skilled in the art should not understand this as a limitation to the present invention.
[0054] As mentioned above, the fifth aspect of the present invention provides a waterproof roll material prepared by the method described in the fourth aspect.
[0055] As mentioned above, the sixth aspect of the present invention provides the application of the waterproof membrane described in the fifth aspect in the field of building waterproofing.
[0056] The present invention will be described in detail below through examples.
[0057] In the following examples, unless otherwise specified, all reagents and raw materials involved are commercially available, all reagents are analytically pure products, and ethanol is anhydrous ethanol.
[0058] In the following examples, unless otherwise specified, each part by weight represents 0.1 kg.
[0059] raw material
[0060] Graphite: purchased from Daikin Corporation of Japan;
[0061] Filler I: Calcium powder: average particle diameter is 10 μm, purchased from Guangzhou Jialiang Company;
[0062] Filler II: Calcium powder: the average particle diameter is 6.5 μm, purchased from Zhenjiang Sentong Calcium Carbonate Factory;
[0063] Fluorosilicone rubber I: extruded fluorosilicone rubber M1050, with a Shore A hardness of 51, a tensile strength of 9.2 MPa, and an elongation at break of 337%, purchased from Wilber New Material Technology Co., Ltd.;
[0064] Fluorosilicone rubber II: extruded fluorosilicone rubber M1070, with a Shore A hardness of 74, a tensile strength of 9.4 MPa, and an elongation at break of 273%, purchased from Wilber New Material Technology Co., Ltd.;
[0065] Silane coupling agent I: KH-550, purchased from Hangzhou Jessica Chemical Co., Ltd.;
[0066] Silane coupling agent II: KH-560, purchased from Hangzhou Jessica Chemical Co., Ltd.;
[0067] Polyolefin elastomer I: melt index is 1.8 g / 10 min, purchased from Dow Chemical, USA;
[0068] Linear low-density polyethylene: density 0.92 g / cm3, melt index 1.6 g / 10 min, purchased from Sinopec Guangzhou Branch;
[0069] Polypropylene: degree of polymerization of 4000-10000, density of 0.89g / cm3, melt index of 3g / 10min, purchased from Fujian Zhongjing Petrochemical Company;
[0070] Cross-linking agent: dicumyl peroxide (DCP), purchased from Anhui Xiangyun Rubber & Plastic Co., Ltd.;
[0071] Cross-linking agent: zinc oxide, purchased from Dalian Jinshi Zinc Oxide Co., Ltd.
[0072] Preparation Example 1
[0073] This preparation example is used to illustrate that the modified fluorosilicone rubber of the present invention is prepared according to the formula and process parameters in Table 1 and the method described below.
[0074] The method for preparing modified fluorosilicone rubber comprises the following steps:
[0075] S1. In the presence of anhydrous ethanol, a silane coupling agent is first mixed with a filler and graphite in a dropwise manner (dropping speed is 0.1 ml / s) to obtain a mixture I; the mixture I is dried at 80° C. for 40 min; the first mixing conditions are: temperature is 70° C., time is 2 h; relative to 100 parts by weight of graphite, the amount of anhydrous ethanol used is 150 parts by weight;
[0076] S2, mixing the fluorosilicone rubber and the mixture I for a second time to obtain a mixture II; the conditions of the second mixing are: temperature of 180° C., time of 10 min, and stirring speed of 50 rpm;
[0077] S3, extruding and pelletizing the mixture II to obtain the modified fluorosilicone rubber.
[0078] Unless otherwise specified, the remaining preparation examples were carried out using a process similar to that of Preparation Example 1, except that the formulas and process parameters used in each preparation example were different, as shown in Table 1 (Note: the parameters not listed in Table 1 are the same as the corresponding parameters in Preparation Example 1).
[0079] Table 1
[0080]
[0081]
[0082] Example 1
[0083] This example is used to illustrate that the waterproof membrane of the present invention is prepared according to the formulation in Table 2 and the method described below.
[0084] The method for preparing the waterproof coiled material comprises the following steps:
[0085] (1) contacting and mixing a composition containing a polyolefin elastomer, a linear low-density polyethylene, a polypropylene, a modified fluorosilicone rubber, a crosslinking agent, and a crosslinking accelerator to obtain an intermediate material; the contacting and mixing conditions are: a temperature of 80° C., a rotation speed of 45 rpm, and a time of 1 hour;
[0086] (2) Extruding and rolling the intermediate material in sequence to obtain the waterproof roll material; the extrusion molding conditions include: the temperature of the three rollers is 45° C., and the gap between the three rollers is 1.5 mm.
[0087] Unless otherwise specified, the remaining examples were carried out using a process similar to that of Example 1, except that the formulations used in each example were different, as shown in Table 2 (Note: the parameters not listed in Table 2 are the same as the corresponding parameters in Example 1).
[0088] Table 2
[0089]
[0090]
[0091] Example 4
[0092] This embodiment is carried out using a process similar to that of Embodiment 1, except that in this embodiment, modified fluorosilicone rubber Z3 of equal mass is used to replace the modified fluorosilicone rubber Z1 in Embodiment 1.
[0093] The rest are the same as in Example 1.
[0094] The waterproof coiled material S4 is prepared.
[0095] Example 5
[0096] This embodiment is carried out using a process similar to that of Embodiment 1, except that in this embodiment, modified fluorosilicone rubber Z4 of equal mass is used to replace the modified fluorosilicone rubber Z1 in Embodiment 1.
[0097] The rest are the same as in Example 1.
[0098] The waterproof coiled material S5 is prepared.
[0099] Example 6
[0100] This embodiment is carried out using a process similar to that of Embodiment 1, except that in this embodiment, modified fluorosilicone rubber Z5 of equal mass is used to replace the modified fluorosilicone rubber Z1 in Embodiment 1.
[0101] The rest are the same as in Example 1.
[0102] The waterproof membrane S6 is prepared.
[0103] Example 7
[0104] This embodiment is carried out using a process similar to that of Embodiment 1, except that, in this embodiment, relative to 100 parts by weight of the polyolefin elastomer I, the content of the linear low-density polyethylene is 65 parts by weight, the content of the polypropylene is 18 parts by weight, the content of the modified fluorosilicone rubber is 15 parts by weight, the content of the cross-linking agent is 5 parts by weight, and the content of the cross-linking accelerator is 5 parts by weight.
[0105] The rest are the same as in Example 1.
[0106] The waterproof membrane S7 is prepared.
[0107] Comparative Example 1
[0108] This embodiment is carried out using a process similar to that of Embodiment 1, except that in this embodiment, modified fluorosilicone rubber DZ1 of equal mass is used to replace the modified fluorosilicone rubber Z1 in Embodiment 1.
[0109] The rest are the same as in Example 1.
[0110] The waterproof membrane DS1 was prepared.
[0111] Comparative Example 2
[0112] This embodiment is carried out using a process similar to that of Embodiment 1, except that in this embodiment, modified fluorosilicone rubber DZ2 of equal mass is used to replace the modified fluorosilicone rubber Z1 in Embodiment 1.
[0113] The rest are the same as in Example 1.
[0114] The waterproof membrane DS2 is prepared.
[0115] Comparative Example 3
[0116] This embodiment is carried out using a process similar to that of Embodiment 1, except that in this embodiment, fluorosilicone rubber I of equal mass is used to replace the modified fluorosilicone rubber Z1 in Embodiment 1.
[0117] The rest are the same as in Example 1.
[0118] The waterproof membrane DS3 was prepared.
[0119] Test Case
[0120] Tensile strength test standard (method): GB / T 328.9-2007 method B.
[0121] Artificial weathering tensile strength test standard (method): according to GB 27789-2011 standard (section 6.17).
[0122] Tensile strength retention test standard (method): Q = (Q2 / Q1) * 100%;
[0123] Where: Q——tensile strength retention rate (%);
[0124] Q2 – tensile strength after artificial weathering;
[0125] Q1——untreated tensile strength;
[0126] Dimensional change rate test standard (method): carried out in accordance with GB / T 328.13 standard.
[0127] S = (S1 - S0) / S0;
[0128] Where:
[0129] S——dimensional change rate, expressed in %;
[0130] S1——size after processing, in millimeters (mm);
[0131] S0——size before treatment, in millimeters (mm);
[0132] The above test method was used to perform performance tests on the waterproof membranes obtained in each example. The test results are shown in Table 3.
[0133] Table 3
[0134]
[0135] It can be seen from the results in Table 3 that the waterproof coiled material prepared by using the modified fluorosilicone rubber provided by the present invention has better tensile strength retention rate and dimensional change rate.
[0136] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing modified fluorosilicone rubber, characterized in that: The method includes: S1, mixing graphite, filler and silane coupling agent for the first time to obtain a mixture I; the conditions of the first mixing include: a temperature of 65-75° C. and a time of 1.5-3 h; S2, mixing the fluorosilicone rubber and the mixture I for a second time to obtain a mixture II; the conditions of the second mixing include: a temperature of 165-190° C. and a time of 5-20 min; S3, extruding and pelletizing the mixture II to obtain the modified fluorosilicone rubber; Relative to 100 parts by weight of the fluorosilicone rubber, the amount of the filler is 10-20 parts by weight, the amount of the graphite is 1-10 parts by weight, and the amount of the silane coupling agent is 1-3 parts by weight.
2. The method according to claim 1, characterized in that: The fluorosilicone rubber has a Shore A hardness of 40-60, a tensile strength of 9-10 MPa, and an elongation at break of 300%-400%; And / or, the average particle diameter of the filler is 7-13 μm; preferably, the filler is calcium powder; And / or, the silane coupling agent is a silane coupling agent with an amino functional group.
3. The modified fluorosilicone rubber prepared by the method according to claim 1 or 2.
4. A sizing composition for waterproof coiled material, characterized in that: The composition contains the following components which are stored independently or in combination: Polyolefin elastomer, linear low-density polyethylene, polypropylene, modified fluorosilicone rubber, crosslinking agent, crosslinking accelerator; Relative to 100 parts by weight of the polyolefin elastomer, the content of the linear low-density polyethylene is 35-65 parts by weight, the content of the polypropylene is 2-18 parts by weight, the content of the modified fluorosilicone rubber is 1-15 parts by weight, the content of the crosslinking agent is 1-5 parts by weight, and the content of the crosslinking accelerator is 0.5-5 parts by weight; The modified fluorosilicone rubber is the modified fluorosilicone rubber described in claim 3.
5. The composition according to claim 4, characterized in that Relative to 100 parts by weight of the polyolefin elastomer, the content of the linear low-density polyethylene is 40-60 parts by weight, the content of the polypropylene is 5-15 parts by weight, the content of the modified fluorosilicone rubber is 3-10 parts by weight, the content of the crosslinking agent is 1-3 parts by weight, and the content of the crosslinking promoter is 0.5-3 parts by weight.
6. The composition according to claim 4 or 5, characterized in that The melt index of the polyolefin elastomer is 1.0-4.0 g / 10 min; And / or, the degree of polymerization of the polypropylene is 4000-10000, the density is 0.88-0.92 g / cm3, and the melt index is 2.0-4.0 g / 10min; And / or, the linear low-density polyethylene has a density of 0.90-0.94 g / cm3 and a melt index of 1.0-4.0 g / 10 min.
7. A method for preparing a waterproof coiled material, characterized in that: The method is carried out using the composition described in any one of claims 4 to 6, comprising: (1) contacting and mixing a composition containing a polyolefin elastomer, a linear low-density polyethylene, a polypropylene, a modified fluorosilicone rubber, a crosslinking agent, and a crosslinking accelerator to obtain an intermediate material; (2) The intermediate material is sequentially extruded, molded, and rolled up to obtain the waterproof roll material.
8. The method according to claim 7, characterized in that The contact mixing is carried out under stirring conditions, and the contact mixing conditions include: temperature of 60-100° C., rotation speed of 30-60 rpm, and time of 0.5-1.5 h.
9. The waterproof roll prepared by the method of claim 7 or 8.
10. Use of the waterproof membrane according to claim 9 in the field of building waterproofing.
Citation Information
Patent Citations
Preparation method for weather-resistant PE sheath material for photoelectricity
CN110982160A
Compounded rubber
CN104046029A
Oil-resistant ethylene propylene diene monomer rubber / POE waterproof coiled material and preparation method thereof
CN106117828A
Highly-clean rubber composition and preparation method thereof
CN106189242A
High stability conductive elastomer for electromagnetic shielding and preparation method thereof
CN107652688A